The Ticking of the Epigenetic Clock: Antipsychotic Drugs in Old Age - Sfera, Adonis; Osorio, Carolina; Inderias, Luzmin; Cummings, Michael (Frontiers in Endocrinology, 2016)
Abstract Background: Exposed to antipsychotic drugs (APDs), older individuals with dementing illness are at risk of cerebrovascular adverse effects (CVAE), including sudden death. Transient microvascular dysfunctions are known to occur in younger persons exposed to APDs, however they seldom progresses to CVAE, suggesting that APDs alone are insufficient for engendering this untoward effect. It is, therefore believed that a preexistent microvascular damage is necessary for CVAE to take place, but the exact nature of this lesion remains unclear. CNS small vessel disease (SVD) is a well-known age-related risk factor for strokes, dementia and sudden death, which may constitute the initial CVAE-predisposing pathology. We therefore propose a two strike CVAE paradigm in which SVD represents the first strike, while exposure to APDs, the second. In this model, both strikes must be present for CVAE to take place, and the neuroimaging load of white matter hyperintensities (WMH) may be directly proportional with the CVAE risk. To investigate this hypothesis at the molecular level, we focused on a seemingly unrelated phenomenon: both APDs and SVD were found protective against a similar repertoire of cancers and their spread to the brain (1-4). Since microRNA-29 has shown efficacy against the same malignancies, and has been associated with small vessels pathology, we narrowed our search down to this miR, hypothesizing that the APDs mechanism of action includes miR-29 up-regulation, which in turn facilitates the development of SVD. Aim: to assess whether miR-29 can be utilized as a peripheral blood biomarker for SVD and CVAE risk. Method: we conducted a search of experimentally verified miR-29 target genes utilizing the public domain tools miRanda, RNA22 and Weizemann Institute of Science miRNA Analysis. We identified in total 67 experimentally verified target genes for miR-29 family, 18 of which correlate with microvascular integrity, and may be relevant for CVAE. Conclusion: Up-regulated microRNA-29 silences the expression of 18 genes connected with capillary stability, engendering a major vulnerability for SVD (first strike) which in turn increases the risk for CVAE after exposure to APDs (second strike).